Sustainable Ecosystem Services Framework for Tropical Catchment Management: A Review - N., Zafirah; N. A., Nurin; M. S., Samsurijan; M. H., Zuknik; M., Rafatullah; M. I., Syakir (MDPI, 2017)
The monsoon season is a natural phenomenon that occurs over the Asian continent, bringing extra precipitation which causes significant impact on most tropical watersheds. The tropical region’s countries are rich with natural rainforests and the economies of the countries situated within the region are mainly driven by the agricultural industry. In order to fulfill the agricultural demand, land clearing has worsened the situation by degrading the land surface areas. Rampant land use activities have led to land degradation and soil erosion, resulting in implications on water quality and sedimentation of the river networks. This affects the ecosystem services, especially the hydrological cycles. Intensification of the sedimentation process has resulted in shallower river systems, thus increasing their vulnerability to natural hazards (i.e., climate change, floods). Tropical forests which are essential in servicing their benefits have been depleted due to the increase in human exploitation. This paper provides an overview of the impact of land erosion caused by land use activities within tropical rainforest catchments, which lead to massive sedimentation in tropical rivers, as well as the effects of monsoon on fragile watersheds which can result in catastrophic floods. Forest ecosystems are very important in giving services to regional biogeochemical processes. Balanced ecosystems therefore, play a significant role in servicing humanity and ultimately, may create a new way of environmental management in a cost-effective manner. Essentially, such an understanding will help stakeholders to come up with better strategies in restoring the ecosystem services of tropical watersheds.